A Comparison of Strengths and Interests Protocols in Career Assessment and Counseling. (November 2016) - Owens, Rhea L.; Motl, Thomas C.; Krieshok, Thomas S.
This study examined the relative performance of three career counseling protocols: a strengths-based protocol, an interest-based protocol, and a protocol that combined strengths and interests. Outcome measures included career exploration, occupational engagement, career decision self-efficacy, hope, positive and negative affect, and life satisfaction pre- and post-intervention. The participants consisted of 82 undergraduate students enrolled in a career and life-planning course. Each participant received a career counseling intervention and a Strong Interest Inventory (SII), StrengthsFinder, or both the SII and StrengthsFinder interpretation. While all three groups showed significant gains from pretest to posttest on most outcomes, results suggest the interests protocol (IP) was the most effective approach when considering the conservation of resources. However, results also merit further exploration of the combined protocol (CP; strengths plus interests) given the greatest gains were achieved by this approach on all but one construct, though not significantly different from the IP. Implications are discussed.